A contribution from Barn Owl pellets analysis to known micromammalian distributions in Buenos Aires province, Argentina - Teta, P. (2010)
Fil:González-Fischer, C.M. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.